Sense of community and citizen participation in neighborhood council in Iran - Barati, Zinab; Abu Samah, Bahaman; Ahmad, Nobaya (Marsland Press, 2012)
This paper was explored to understand the effects of sense of community on citizen participation in Neighborhood Councils of Tehran city, Iran. There is a variation in study results regarding citizen participation, therefore understanding the effective factors (e.g. sense of community) can help to make citizen participation efforts successful in neighborhood organization. The analysis of data uses SEM to determine the effects of sense of community on citizen Participation in neighborhood organization. The findings revealed that 66% variance in citizen participation explained by sense of community. The findings of the study imply that residents who have a sense of community with their neighbors are more likely to participate in neighborhood associations.